PSYCHOLOGICAL MECHANISMS OF CRIME PREVENTION AMONG TEENAGERS (FAMILY ASPECT) (American Journal of Interdisciplinary Research and Development, 2022)
This article analyzes the causes and factors of juvenile delinquency based on the results and conclusions of research by educators and psychologists. The article is devoted to the family aspect and gives recommendations for the prevention of juvenile delinquency.